Control of Vibrio alginolyticus in Artemia culture by treatment with bacterial probiotics - Mohd. Shukri, Nurul Shazwani (2013)
Probiotics are bacteria which can act as health promoter of other organism by modifying the ambient microbial community, enhancing feed nutritional value, enhancing the host response towards disease, or improving the quality of its ambient environment. Probiotics Micrococcus spp. (JAQ07) and Bacillus spp. (JAQ04) were used as potential probiotics in this experiment. Both probiotics were identified as Gram-positive with different morphology. Micrococcus spp. was a rod-shaped bacterium whereas Bacillus spp. was cocci-shaped bacterium. In in-vivo assay, Artemia was used as a host and treated with Bacillus spp. and Micrococcus spp. at different concentrations (102, 104 and 106 CFU ml-1) and then challenged with Vibrio alginolyticus at concentration 105 CFU ml-1. Bacillus spp. able to enhance the survival of Artemia better compared with Micrococcus spp. when challenged with Vibrio alginolyticus. Artemia treated with Bacillus spp. at concentration of 106 CFU/ml and challenged with Vibrio alginolyticus showed 70% of survival compared with the survival of challenged Artemia with Vibrio alginolyticus only (20% survival rate) after 7 days. Meanwhile Artemia pre-incubation with Micrococuss spp. and challenged with Vibrio alginolyticus showed 68% survival. Both probiotics are not harmful because no significant of survival was found compared to the control. Micrococcus spp. was able to slightly reduce the vibrios load in Artemia and culture water. However, Bacillus spp. was not able to reduce the vibrios load in water culture and Artemia. Nevertheless, both demonstrated good characteristics as probiotic candidates for aquaculture.